Prevalence of iodine deficiency disorders among 6 - 12 years school children of Gulbarga city - P M, Raveesh P M; G, Ajay Kumar; G, Boramma; Reddy, Srinivas; Kapate, Rajashekhar (Indian Journal of Community Health, 2014)
Introduction: Iodine Deficiency Disorders is among the easiest and least expensive of all nutrient disorders to prevent. Salt iodization is currently the most widely used strategy to control and eliminate Iodine Deficiency Disorders. The Central Government has issued the notification banning the sale of non-iodated salt for direct human consumption in the entire country with effect from 17th May, 2006 under the Prevention of Food Adulteration Act 1954. Rationale: 6 out of 17 districts surveyed in Karnataka were endemic to Iodine deficiency with goiter prevalence rates in the range of 10.67–41.11%. In Gulbarga more than 90% of the families were consuming salt with Iodine content less than 15 ppm. Objectives: To assess the magnitude of the Iodine Deficiency Disorders among the children. To determine the Iodine content of the salt used at houses of the children and to find out the availability of adequately iodized salt at the retail shops. Materials and Methods: A cross sectional study among 6-12 Years School Children conducted in Gulbarga city. Cluster sampling methodology and surveillance methods for iodine deficiency disorders as recommended by WHO/ICCIDD were used. The study included 1620 school children with equal proportion of girls and boys. The salt samples were tested on spot with MBI kit provided by UNICEF, and Iodine concentration was recorded as 0, <15 and >15 ppm. Results: The overall prevalence of goitre was 4.32%, there was no significant gender variation in total goitre prevalence. The association between anaemia and the prevalence of total goitre was statistically significant. Proportion of the children consuming adequately iodised salt was 51.1%. Among salt samples collected from retail shops, only 44.62% samples were adequately iodised. Conclusion: prevalence of goitre was 4.32% which is below the cut-off to indicate endemicity of IDD. Adequately iodised salt availability and consumption among household is not satisfactory.